A Redox‐Activated MRI Contrast Agent that Switches Between Paramagnetic and Diamagnetic States1. Issue 52 (12th November 2013) - Tsitovich, Pavel B.; Spernyak, Joseph A.; Morrow, Janet R.
<x xml:space="preserve">Abstract</x> Trigger ready: A redox‐activated MRI contrast agent can cycle between paramagnetic CoII (MRI‐active) and diamagnetic CoIII (MRI‐silent). The paramagnetic CoII form produces a highly shifted CEST signal at 135 ppm (37 °C). The redox state of the Co complex is altered by O2 partial pressure and reductant concentration (thiols) on a time scale relevant to imaging. MT=magnetization transfer.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>